High Power Diode Lasers Technology and Applications - Bachmann, Friedrich; Loosen, Peter; Poprawe, Reinhart (Springer Series in Optical Sciences, 2007)
In a very comprehensive way this book covers all aspects of high power diode laser technology for materials processing. Basics as well as new application oriented results obtained in a government funded national German research project are described in detail. Along the technological chain after a short introduction in the second chapter diode laser bar technology is discussed regarding structure, manufacturing technology and metrology. The third chapter illuminates all aspects of mounting and cooling, whereas chapter four gives wide spanning details on beam forming, beam guiding and beam combination, which are essential topics for incoherently coupled multi-emitter based high power diode lasers. Metrology, standards and safety aspects are the theme of chapter five. As an outcome of all the knowledge from chapter two to four various system configurations of high power diode lasers are described in chapter six; not only systems focussed on best available beam quality but especially also so called "modular" set-ups are considered, where assemblies adapted to special applications are chosen. Finally, a wide field of applications, performed with the systems described in chapter six is described in chapter seven.